2020
DOI: 10.3390/jsan9030043
|View full text |Cite
|
Sign up to set email alerts
|

Where Freshness Matters in the Control Loop: Mixed Age-of-Information and Event-Based Co-Design for Multi-Loop Networked Control Systems

Abstract: In the design of multi-loop Networked Control Systems (NCSs), wherein each control system is characterized by heterogeneous dynamics and associated with a certain set of timing specifications, appropriate metrics need to be employed for the synthesis of control and networking policies to efficiently respond to the requirements of each control loop. The majority of the design approaches for sampling, scheduling, and control policies include either time-based or event-based metrics to perform pertinent actions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Multiple studies demonstrate that explicitly taking into account the dynamics of the state and recognizing its significance for control objectives results in improved control performance [35], [36]. Studies have shown the effectiveness of semantic metrics, other than age, in wireless resource scheduling at the medium access control (MAC) layer.…”
Section: Towards the Next-generation Intelligent Communications And N...mentioning
confidence: 99%
“…Multiple studies demonstrate that explicitly taking into account the dynamics of the state and recognizing its significance for control objectives results in improved control performance [35], [36]. Studies have shown the effectiveness of semantic metrics, other than age, in wireless resource scheduling at the medium access control (MAC) layer.…”
Section: Towards the Next-generation Intelligent Communications And N...mentioning
confidence: 99%
“…The authors of [3] look at a cross-layer design of communication and application aspects considering the synthesis of multi-loop controllers for heterogeneous Linear Time-Invariant (LTI) systems explicitly. Classic design approaches for sampling, scheduling, and control policies include either time-based or event-based metrics to perform appropriate actions in response to the changes of the parameters of interest.…”
Section: Summary Of Contributionsmentioning
confidence: 99%
“…Classic design approaches for sampling, scheduling, and control policies include either time-based or event-based metrics to perform appropriate actions in response to the changes of the parameters of interest. The proposed solution in [3] specifically focuses on the combination of a time-based metric, namely the Ageof-Information, and a threshold-based triggering function. The control performance is measured by Linear-Quadratic Gaussian (LQG) cost functions.…”
Section: Summary Of Contributionsmentioning
confidence: 99%
“…From the existing literature, we know that minimizing AoI as a standalone metric is sub-optimal when it comes to NCS scenarios with heterogeneous control loops [11]. Therefore, control-aware age-penalty functions have been derived and employed to take optimal decisions [12]- [14] in wireless networked control systems. In [12] authors study a centralized resource allocation problem for multiple, heterogeneous feedback control loops.…”
Section: Introductionmentioning
confidence: 99%
“…Under the assumption that sensors are able to replace outdated packets in their transmission queue, they obtain an optimal, stationary scheduling policy by solving a discounted cost minimization problem. In [13] and [14] authors derive optimal sampling policies in the context of NCS, where they employ control dependent age-penalty functions as a metric. Similar to [12], those works assume that sensors are always able to replace any outdated packet in the transmission queue with a fresher incoming packet and thus assume zero queuing delay.…”
Section: Introductionmentioning
confidence: 99%